Efektivitas Promotion Mix Terhadap Keputusan Wali Murid Memilih SMA IT Pesantren Nururrahman - T Husain (MBIA, 2017)
This research aim was to obtain empirical evidence and analyzing the effectiveness of promotional mix on decision parents in choosing a school. The research type was causality using survey approach. The population of this research was candidate parents who purchased the form registering student new admission (PPDB) in school year of 2016/2017 as many as 217 people. The number of samples was counted 69 peoples. Data was collected through observation and questionnaire-based. The data analysis method used structural equation model based on regression variance with partial least square approach. The results of this research indicated that only word-of mouth marketing components of promotional mix had significant effect to the decision parent. Promotional mix was started from advertising to establish brand awareness, public relations and direct marketing activities to shape consumer behavior, the role of word-of mouth marketing and terminate in personal selling activities to determine purchase decisions.